Waste Controller Boat by Bluetooth Applications - Suhaimi, Muhammad Aiman Shahrul; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2021)
Ecosystem like lakes, river and ocean are precious to us. This ecosystem is needed to be protected to make sure it can live without any damages or for long time. So, our government and non-government-organizations (NGO) had made many efforts to serve or protect this ecosystem. The efforts that had been made is by using a technology robotic like an Interceptor to clean up the waste that had been made by human on the ecosystem like big river, big lake and ocean. How about the small area like small river and small waterways area? How can they be conserves and protect? In order to solve this problem, inspired by the technology of the Interceptor the Waste Controller Boat by Bluetooth Applications project is proposed. This project functionally to help cleaning the waste on the small area by collecting the waste on the water surface of the area through the Bluetooth apps. The method of this project uses the Bluetooth application to control the project prototype by using smartphone. In developing the project, there a few steps involve which is software development and hardware development. In software development, there are few software used like fritzing to design the circuit, sketch-up to design 3D model of prototype, Arduino IDE to upload code or instructions program on Arduino and Arduino Bluetooth control to connect the smartphone and the prototype. In hardware development, the prototype project was made of recycle material or unused material. The prototype hardware is believed can move well on water surface and able to collect the waste on the water surface.